(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Stunting is a current issue that is of global concern, especially in Indonesia to face a window opportunity in 2030. A number of stunting prevention and management methods have been attempted to encourage knowledge and fulfillment of nutrition in preventing chronic malnutrition that causes stunting, including stunting prevention education for caten , nutrition education in fulfilling energy in pregnant women. Pregnant women are a vulnerable group with nutritional problems, this is related to the process of fetal growth and physiological changes in various organs of the body to support the pregnancy process Objective: This study generally aims to determine the effect of health education on knowledge about stunting in pregnant women in Bangunharjo Village, Kapanewon Sewon, Bantul Regency. Method: This study used a quasi-experimental research method (quasi-experimental) with a "one group pretest-posttest design". This research activity provides treatment in the form of health education regarding stunting to find out a symptom of influence that arises after being given treatment. The subjects of this study were 51 pregnant women in Bangunharjo Village, Kapanewon Sewon, Bantul Regency. Results: The results of the research from the paired t-test showed a t-test value of 7.023 with a p-value of 0.000, which means that there is a significant difference between pregnant women’s knowledge about stunting before and after counseling. Keywords: Knowledge of Stunting, Pregnant Women, Health Education